(untitled) (Journal of Legal Studies, 2024)
This article examines the socio-legal aspects of the formation of the concept of a traffic accident, exploring its evolution from the late 19th century to the present day. The rapid growth of motor vehicles and the increasing complexity of road systems have necessitated the development of legal frameworks and safety regulations to address the risks posed by traffic accidents. The study highlights key legal milestones, such as the official introduction of the term "traffic accident" at the 1949 Geneva Conference, and analyzes the role of societal attitudes toward road safety and personal responsibility. It also delves into the cultural factors influencing traffic behavior, emphasizing the need for a comprehensive safety culture that involves drivers, pedestrians, and state regulation. By assessing the socio-legal dynamics, the article provides insights into the challenges of ensuring road safety and reducing the social and economic consequences of traffic accidents.